Optimizing learning engagement and performance in technical education: Harnessing the power of video tutorials for enhanced motivation and skill development in Shield Metal Arc Welding Subject - Hafis, M; Syahril, Syahril; Refdinal, Refdinal; Prasetya, Febri (Researcher and Lecturer Society, 2023)
This study aimed to enhance the quality of Shield Metal Arc Welding instruction in Class XI Welding Engineering at State Vocational High School 1 Bukittinggi through the integration of interactive media videos. Employing a class action research design with saturated sampling, the research findings revealed that the implementation of video tutorials significantly improved student motivation and learning outcomes. The use of video tutorials captured students' interest, resulting in increased motivation for learning Shield Metal Arc Welding. In the initial cycle, student motivation in Class XI Welding Engineering at State Vocational High School 1 Bukittinggi, as measured in meeting I, stood at 54%, indicating a less motivated state. By meeting II of cycle I, the motivation increased to 61%, categorized as moderately motivated. In the subsequent cycle, meeting I recorded a motivation level of 72%, demonstrating a motivated state, while meeting II in cycle II reached 82%, indicating a highly motivated state. Consequently, there was a noticeable progression in student learning motivation from cycle I to cycle II. Furthermore, student learning outcomes in Shield Metal Arc Welding for Class XI Welding Engineering at State Vocational High School 1 Bukittinggi improved when videos were utilized as interactive media. In cycle I, the average student learning outcome was 77.88, categorized as moderate. In cycle II, the average increased to 79.06, reflecting a high level of achievement. This indicates a positive shift in student learning outcomes, moving from moderate to good performance.